2018
DOI: 10.3390/rel10010004
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Bodies in Early South Asian Buddhism: Some Relics and Their Sponsors According to Epigraphy

Abstract: Some of the earliest South Asian Buddhist historical records pertain to the enshrinement of relics, some of which were linked to the Buddha and others associated with prominent monastic teachers and their pupils. Who were the people primarily responsible for these enshrinements? How did the social status of these people represent Buddhism as a burgeoning institution? This paper utilizes early Prakrit inscriptions from India and Sri Lanka to reconsider who was interested in enshrining these relics and what, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…cakravartin, wheel-turning king) named Daḷhanemi and his eight successors. Historically and according to legend, Daḷhanemi's character is affectionately modelled after King Aśoka of the Mauryan dynasty of the third century BCE-the famous and premier example of such a sovereign and ideal patron (Milligan 2019a). Using these kings as examples, the Buddha describes the linkage between kingly virtue and the subjects' life within the kingdom.…”
Section: Money Matters: Dāna and Wealth In The Pāli Canonmentioning
confidence: 99%
“…cakravartin, wheel-turning king) named Daḷhanemi and his eight successors. Historically and according to legend, Daḷhanemi's character is affectionately modelled after King Aśoka of the Mauryan dynasty of the third century BCE-the famous and premier example of such a sovereign and ideal patron (Milligan 2019a). Using these kings as examples, the Buddha describes the linkage between kingly virtue and the subjects' life within the kingdom.…”
Section: Money Matters: Dāna and Wealth In The Pāli Canonmentioning
confidence: 99%
“…More recent literature shows an increasing academic interest on the aesthetics of Buddhism in a wider range of disciplines, such as art and design (Song et al 2018), psychotherapy (Cormack et al 2018), cognitive engineering (Van Dam et al 2018), ecology (Lim 2019), business (Lucas 2018;Milligan 2018) and so forth. For example, Macmillan (2006) suggested that superior design is not just about the aesthetic improvement of the quality of our lives; it is also about the value created for the viewers.…”
Section: Introductionmentioning
confidence: 99%